Preparation of lentil and quinoa protein complexes through protein–protein interactions and water kefir–assisted fermentation to improve protein quality and functionality - Alrosan, Mohammad; Tan, Thuan-Chew; Mat Easa, Azhar; Gammoh, Sana; Alu'datt, Muhammad H.; Tranchant, Carole C.; Almajwal, Ali Madi; Maghaydah, Sofyan; Dheyab, Mohammed Ali; Jameel, Mahmood S.; Al-Qaisi, Ali; Al Qudsi, Farah R. (Frontiers in Sustainable Food Systems, 2023)
Industrial applications of lentil (LP) and quinoa (QP) proteins are limited due to their relatively poor water solubility. In this study, a combination of protein-protein interaction (PPI) and fermentation was used to improve the functionality and nutritional value of LP by conjugating them with QP. The reaction conditions between LP and QP for producing these conjugates were established. The ratio of LP to QP was equal (50:50) and complexation was carried out at 25 ºC for 60 min. Fermentation of the solubilized LP-QP complexes (1%, w/v) for 5 days at 25 ºC with water kefir (5%, v/v) was carried out to enhance the protein quality and functionality of the LP-QP complexes. The combined technique significantly enhanced protein digestibility, decreased the proportion of -helices in the protein structure in favour of random coil components, and improved the phenolic content of the LP-QP complexes. Digestibility increased to 87%, up from 76% for unfermented LP-QP. Moreover, the LP-QP complexes produced using the combined technique generated a highly nutritional protein with a reduced saponin content. This research revealed that a combination of PPI and water kefir fermentation significantly enhances the nutritional and functional quality of LP, creating new opportunities for leveraging the growing popularity of plant-based proteins into high-value industrial applications.